Stereoselective Steady‐State Disposition and Bioequivalence of Brand and Generic Bupropion in Adults. Issue 5 (30th June 2020) - Kharasch, Evan D.; Neiner, Alicia; Kraus, Kristin; Blood, Jane; Stevens, Angela; Miller, J. Philip; Lenze, Eric J.
Abstract : The antidepressant bupropion is stereoselectively metabolized and metabolite enantiomers have differential pharmacologic effects, but steady‐state enantiomeric disposition is unknown. Controversy persists about bupropion XL 300 mg generic equivalence to brand product, and whether generics might have different stereoselective disposition leading to enantiomeric non‐bioequivalence and, thus, clinical nonequivalence. This preplanned follow‐on analysis of a prospective, randomized, double‐blinded, crossover study of brand and 3 generic bupropion XL 300 mg products measured steady‐state enantiomeric plasma and urine parent bupropion and primary and secondary metabolite concentrations and evaluated bioequivalence and pharmacokinetics. Steady‐state plasma and urine bupropion disposition was markedly stereoselective, with up to 40‐fold differences in plasma concentrations of the active metabolite S, S ‐hydroxybupropion vs. R, R, ‐hydroxybupropion. Urine metabolite glucuronides were prominent, but glucuronidation was metabolite‐specific and enantioselective. There were no differences between any generic and brand, or between generics, in plasma enantiomer concentrations of bupropion or the major metabolites. All generic products satisfied formal bioequivalence criteria (peak plasma concentration (Cmax ) and area under the plasma concentration‐time curve over 24 hours (AUC0–24 )) using enantiomers for bupropion as well as for metabolites, and generics were comparable to each other, and were considered bioequivalent, based on enantiomeric analysis. Enantiomeric bioequivalence explains the previously observed therapeutic equivalence of bupropion generics and brand in treating major depression. These results have important implications for understanding the clinical therapeutic effects of bupropion based on complex and stereoselective metabolism.